(untitled) (Jurnal Pilar Nusa Mandiri, 2014)
A hospital or clinic health is one organization that provides service examination for a sick man. Medical rolling is note or history about disease history ever suffered in by patients who shall contain data about the date of the examination, physician who, silvana diagnose, and medicine was given. Along with the progress of the times and public knowledge about health services especially the need for information, to achieve a service good health, a hospital or clinic must be supported by the system qualified capable of regulating and manage data for source of information. A hospital or clinic requires the existence of a system precise information and reliable. The existing system is still done conventionally or paper, still use media from data management patients medic, rolling payment transaction until making reports, needed at a particular period allowing unfolding process occurring at the time of registration, errors in lacking accurate report made and delay in search of the data needed. The design program is the best solution to resolve questions that were at this clinic. With the design information systems rolling expected to ease medical officer in performing its duties with more effective and efficient compared with the previous system for increasing, productivity health services work in achieving excellence.